Manajemen Sumber Daya Manusia Kepala Sekolah/Madrasah dalam Meningkatkan Mutu Pendidikan - Kodiran, Kodiran (Universitas Islam Negeri Raden Intan Lampung, 2018)
There is no denying that many things happen before us, especially in the eduation world, there is something called mall practice value, there are mallpractice offices and a myriad of designations which are certainly difficult to express again. And what is worse is the title of headmaster for life, because the headmaster is close to the dection maker,there is also the term headmaster for corn, because the headmater is not close to the direct decision-making boss, there are also those who justify any means to boost it he can be the head of the school with slander there, slander here, menzolimi there menzolimi here long as the goal is achieved.If this country wants to advance and produce human beings who have good souls, it must start from humanizing humans, and can appreciate the achievementsof the tachers who will become principals, not legalize whois near the boss who will win firever-forever,as if this country will embace the jungle system who is strong who wins,who is close to the official who is in the mood,not one or two principal who have reached tens of years have not been replaced, and as f all eyes were blinded, and tongue to voice, even though the president, the education minister and the minister of religion have been replaced, there are still principals/ madrasahs who are still hanging out in office, even though they are not principals at all.